Endoscopic decompression of the optic nerve in patients with post-traumatic vision impairment - Sieśkiewicz, Andrzej; Łysoń, Tomasz; Mariak, Zenon; Rogowski, Marek (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: Traumatic optic neuropathy (TON) is a dangerous complication of head trauma but the mechanism of the symptoms still remains obscure. Moreover, there is no uniformly accepted treatment protocol for this condition. Endoscopic, minimally invasive decompression of the optic nerve in its bony canal is an alternative to conservative approach. Material and methods: Endoscopic optic nerve decompression was performed in 6 patients, whom head trauma caused blindness or severe impairment of vision. In 5 of them direct optic nerve injury might have been suspected due to presence of bony fractures in the region of the optic canal and the orbital apex. The time from the trauma to the surgical intervention varied from 8 hours to 30 days. All the patients before the attempted surgery were treated with steroids, however the doses and time of this treatment varied significantly. Results: There were no complications of the surgery; all the patients were mobilized on the day of operation and reported no problems with nasal breathing. Vision improved in 2 of 6 patients (33.3%), interestingly both of them had experienced rather gradually developing deterioration of vision during several hours after the trauma. Conclusions: Endoscopic optic nerve decompression is a minimally invasive and safe procedure to be employed for optic nerve decompression in patients with posttraumatic impairment of vision.